2022
DOI: 10.1111/1759-7714.14331
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐205‐5p promotes lung cancer progression and is valuable for the diagnosis of lung cancer

Abstract: Background: MicroRNAs (miRNAs) function as potential diagnostic biomarkers in various cancers. This study aimed to evaluate the roles of miR-205-5p in lung cancer progression and diagnosis. Materials and Methods: MiR-205-5p was detected by quantitative real-time PCR. The effect of miR-205-5p on cell proliferation and metastasis was estimated by MTT and flow cytometry. The expression of TP53INP1 and related genes was analyzed by immunoblotting. The diagnostic value of miR-205-5p was analyzed using receiver oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Our deep sequencing analyses have shown that miR-205-5p exhibits a higher expression level in lung tumor tissues compared with noncaseous lung tissues and could provide a potential biomarker for NSCLC (Li et al, 2017; Ma et al, 2014; Xing et al, 2010). Upregulation of miR-205-5p contribute to lung cancer cell proliferation and metastasis in vitro and in vivo , by regulating functions of TP53INP1, RB1, and P21(Zhao et al, 2022). Aberrant miR-210-3p expression in body fluids could diagnose several types of malignancies, including lung cancer (Papaconstantinou et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our deep sequencing analyses have shown that miR-205-5p exhibits a higher expression level in lung tumor tissues compared with noncaseous lung tissues and could provide a potential biomarker for NSCLC (Li et al, 2017; Ma et al, 2014; Xing et al, 2010). Upregulation of miR-205-5p contribute to lung cancer cell proliferation and metastasis in vitro and in vivo , by regulating functions of TP53INP1, RB1, and P21(Zhao et al, 2022). Aberrant miR-210-3p expression in body fluids could diagnose several types of malignancies, including lung cancer (Papaconstantinou et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-205-5p functioned as a tumor promoter in many cancers, including ovarian cancer [ 21 ] and lung cancer [ 22 ]. On the contrary, many studies showed that miR-205-5p was downregulated in thyroid cancer, and its upregulation suppressed cell proliferation and invasion [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the survival fraction of NPC cells were decreased, and the SER ratio was increased after RAE treatment, confirming that RAE enhanced NPC cell radiosensitivity. MiR-205-5p functioned as a tumor promoter in many cancers, including ovarian cancer [21] and lung cancer [22]. On the contrary, many studies showed that miR-205-5p was downregulated in thyroid cancer, and its upregulation suppressed cell proliferation and invasion [23].…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐130b‐5p is known to accelerate cell migration and proliferation in gastric cancer (Chen et al, 2018). MiR‐205‐5p is a valuable diagnostic marker in lung cancer and a protective factor in gastric cancer, which suppresses angiogenesis in gastric cancer through downregulation of VEGFA and FGF1 (Zhang et al, 2021; Zhao et al, 2022). The results mentioned above exhibited that our regulatory network was closely related to the progression of cancer, and six key miRNAs were modulated by CNV‐driven lncRNAs, which may be novel biomarkers for LUSC.…”
Section: Discussionmentioning
confidence: 99%